Public oral health policies for children: historical perspective, state of the art and future challenges (Research, Society and Development, 2020)
The present study analyzed the primary health care policies aimed at Pediatric Dentistry, identifying the trajectory, the formation of the political agenda and the challenges, from 1912 to 2020. The strategy of searching for legal documents was carried out in the digital collection of the Ministry of Health, in the Federal Official Gazette and in the Legislation Portal. The articles were searched in the VHL and SciELO, using the descriptors: public health policies, oral health, children and schoolchildren, associated with each other. 356 articles were found and, after analysis, 35 were selected to compose this study. In addition, 18 legal documents and secondary data from oral health surveys were used to compose this historical line. It was found that children's access to public dental care was prioritized by the incremental model, based on the curative and interventionist logic. However, with the adoption of an expanded conception of the health-disease process, there was a need to adapt scientific dentistry to a model that privileges prevention and health promotion, expressing itself through integral models, inversion of attention, attention early, until reaching the current model of universal and egalitarian character that affects the public sphere. Despite the increase in the offer of access to clinical and educational actions aimed at this public, the prevalence of the main oral health problems is still far from acceptable levels, and it is evident how the oral health policies aimed at children are subordinate to the will policy of successive governments, and such actions must be assimilated as State policy, resolving the variability resulting from changes in the political-democratic-governmental scenario.